2015
DOI: 10.1155/2015/758684
|View full text |Cite
|
Sign up to set email alerts
|

Levonorgestrel Inhibits Human Endometrial Cell Proliferation through the Upregulation of Gap Junctional Intercellular Communication via the Nuclear Translocation of Ser255 Phosphorylated Cx43

Abstract: Objects. To assess whether LNG exerts antiproliferation effects on human endometrial cells through changes of GJIC function and the phosphorylated Cx43. Methods. Cell proliferation and apoptosis of human endometrial stromal cells (HESCs) and glandular cells (HEGCs) treated with LNG in a dose- and time-dependent manner. GJIC change and further total Cx43 and serine 368 and 255 phosphorylated Cx43 were measured. Results. 5 × 10−5 mol/L LNG revealed a time-dependent inhibition of cell proliferation and an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…A similar effect was noticed for LNG. In an in vitro study, the apoptosis rate in endometrial cancer cells increased after the 24 h treatment with 5 × 10 −5 M LNG [ 62 ]. A recent in vivo study showed that the oral administration of EE-LNG can modulate apoptosis marker genes, down-regulating the Bcl-2, and up-regulating the Caspase-1 and -3 expressions in female rats [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar effect was noticed for LNG. In an in vitro study, the apoptosis rate in endometrial cancer cells increased after the 24 h treatment with 5 × 10 −5 M LNG [ 62 ]. A recent in vivo study showed that the oral administration of EE-LNG can modulate apoptosis marker genes, down-regulating the Bcl-2, and up-regulating the Caspase-1 and -3 expressions in female rats [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the location of Cx43 at the nucleus was shown to dynamically change during the mitotic process in lung A549 adenocarcinoma cells [ 569 ]. The nuclear location of Cx43 might be explained by the existence of a putative nuclear-targeting sequence encoded within its CT domain [ 570 , 571 ], and its translocation might depend on phosphorylation at Ser255, as it has been proposed in human endometrial cells [ 572 ]. Furthermore, Wnt signaling has been suggested to regulate translocation of Cx43 from the cytosol to the nucleus in PC3 human prostate cancer cells, where it may constitute a cotranscription factor of β-catenin [ 573 ].…”
Section: Cardiac Connexinsmentioning
confidence: 99%
“…HC opening can be triggered by lowering [Ca 2+ ] e , increasing [Ca 2+ ] i , connexin dephosphorylation, metabolic inhibition, or hyperosmolar conditions, as demonstrated in isolated ventricular cardiomyocytes by dye uptake and electrophysiological methods (Kondo et al, 2000;John et al, 2003;Wang et al, 2012a). Within cardiomyocytes, Cx43 is located also in subsarcolemmal mitochondria (see below) and the CT of Cx43 translocates into the nucleus and inhibits cell proliferation (Dang et al, 2003;Zhao et al, 2015). Cardiac connexins also have extensive nonchannel functions that in many cases link to interactions of the Cx43 CT with various scaffolding and signaling proteins, forming a connexin interactome network or "connexome."…”
Section: Connexins In Cardiac Diseasementioning
confidence: 99%